Excellent cyclic stability of symmetric and asymmetric supercapacitors constructed by graphene deposited Cu and Ni electrodes - Yargi, Onder; Ozmen, Mehmet Murat; Buyukpehlivan, Sude; Gelir, Ali (WILEY, 2022)
Supercapacitors (SC) with ionic liquid bis(trifluoromethanesulfonyl)imide (TFMS) trapped polyacrylamide (PAAM) hydrogel separator between graphene deposited nickel and copper foam electrodes were designed and assembled in CR2032 coin cell. The symmetric and asymmetric SCs were named as G-NiF/G-NiF, G-CuF/G-CuF, and G-NiF/G-CuF where G-NiF, and G-CuF stands for graphene deposited nickel foam and copper foam, respectively. The best electrochemical performance was obtained for G-NiF/G-NiF in terms of higher energy, power, and current densities from the galvanostatic charge-discharge (GCD) and CV curves. Specific capacitances of G-CuF/G-CuF, G-NiF/G-NiF, and G-NiF/G-CuF SCs were found as 8.3, 9.8, and 10.4 F g(-1) at 0.5 mA, respectively. Capacitance retention of both G-NiF/G-NiF and G-NiF/G-CuF SCs does not change and reveals excellent performance of 100% up to 5000 cycles indicating long term stability in SCs applications.
Keywords: coincell; copper; graphene; nickel; PAAM hydrogel; supercapacitor; HIGH-PERFORMANCE SUPERCAPACITOR; NICKEL FOAM; OXYGEN REDUCTION; COPPER FOAM; LITHIUM; CARBON; BATTERY; OXIDE; FABRICATION; NANOSHEETS; Energy & Fuels; Nuclear Science & Technology